Kajian Pemahaman Penumpang Tentang Barang Bawaan yang Dilarang (Prohibited Item) Di Terminal 2 Bandar Udara Internasional Juanda - Ravi Al Farkhan; Kardi Kardi; Dwi Lestary (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
This study aims to analyze passengers' understanding of prohibited items at Terminal 2 of Juanda International Airport and evaluate the effectiveness of information delivery strategies implemented to support aviation safety and security. The research uses a descriptive qualitative method with data collection techniques such as observation, interviews, and documentation. The findings show that most passengers, particularly elderly individuals, still do not have a clear understanding of the difference between items allowed in the cabin and those that must be placed in checked baggage. Information regarding prohibited items is only discovered when passengers reach the security check area (PSCP), which is considered too late, causing panic and discomfort among passengers. The main factor contributing to the low level of understanding is the unstrategic delivery of information and the lack of engaging communication media. Although information about prohibited items is available through posters and announcements, these methods do not effectively attract passengers' attention. Passengers often overlook the information placed in less visible or strategic locations. This indicates that the current information media have not been effective in providing significant impact on passengers' understanding. This study recommends several steps to improve passenger understanding. The placement of more effective information media, such as eye-catching educational banners and 3D video displays at the departure entrance area, is expected to attract more attention from passengers. Additionally, the use of digital platforms, such as airport apps or social media, could be an effective way to deliver information to passengers before they arrive at the airport. With these strategies, passengers can better prepare and avoid potential mistakes during security checks, thus supporting the smoothness and safety of their flights.